ROASTING CONDITIONS AND QUALITY COFFEE: THE EMPIRICALLY OPTIMISED PROCESS - Vakaryk, Nadiia; Sachko, Anastasiia; Sema, Oksana; Gubsky, Sergey; Kobasa, Igor (RIC Pro-Akademia – CC BY, 2023)
The degree of roast, temperature and duration of the roasting phases of the coffee bean directly affect the sensory characteristics of the coffee cup. Therefore, to achieve the best roasting result, it is important to combine the human factor with special software products. To automate the roasting process, the Artisan roasting recording software was used. Automation of roasting allows better reproduction of the process conditions for different coffee samples. However, roasting is a rather complex and multi-stage process, and its automation does not guarantee the full reproduction and disclosure of the taste and aroma properties of the "perfect cup". Therefore, the qualifications, skills and experience of the roaster play a significant role in achieving and further reproducing the desired flavour profile.
Keywords: arabica coffee; robusta coffee; coffee beans; roasting process; temperature; sensory characteristics